Flexural behavior of fiber reinforced lightweight concrete - Alex, Xavier Infant; Arunachalam, Kalidas (Revista de la Construcción. Journal of Construction, 2019)
In this research the flexural behavior of lightweight aggregate concrete with inclusion of steel and glass fiber was investigated. Pumice aggregate was used for the replacement of normal weight aggregate to reduce the density of concrete in order to achieve lightweight concrete. The methodology consisted of comparing the results of conventional reference concrete, plain. Light Weight Aggregate Concrete (LWAC) and fiber reinforced LWAC. The beams were produced with two types of fiber reinforced LWAC, plain LWAC and conventional concrete with similar compressive strength to allow for the comparison of structural performance of the beam. The fibers were added in the LWAC to reduce the brittleness of the concrete in order to increase the energy absorption capacity and to control the faster rate of crack development. In this research steel and glass fibers were added separately in three percentages of 0.5, 1.0 and 1.5 based on the weight of concrete. The hybrid combinations of steel and glass fibers were not adopted in this study. The beam specimen with 20% LWA and 0.5% steel fiber has the increase in load carrying capacity by 28% as compared to control beam.The ductility ratio of the same beam is 85% more than that of control specimen.